Kyai's Position At The Boarding School and Their Implications For Society: Study At Nurul Iman Islamic Boarding School: Study at Pondok Pesantren Nurul Iman - Saidah Ahmad (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
Kyai is a title given by the community to people who are experts in Islamic religious knowledge who have or have become leaders and teach the yellow book at Islamic boarding schools. Kyai is an important element in Islamic boarding schools because Kyai is the sole leader and has high authority. In society, Kyai is a role model, Kyai has an important role in social change in society. The kyai is the main character who is highly respected by the community. Kyai serves as a non-formal leader in society. Serve as a place to ask for opinions and advice if there are problems in the community. This research is qualitative research located at the Nurul Iman Islamic Boarding School. At the Nurul Iman Islamic Boarding School, Kyai is very lacking and is not the sole leader and has high authority. Therefore, efforts are needed to improve the position of Kyai in Islamic boarding schools.